The Last Chess Game: Computers, Media Events, and the Production of Spectacular Intelligence. - Hamilton, Sheryl N. (Canadian Review of American Studies, 2000)
Examines the 1996 and 1997 chess matches between Garry Kasparov and the IBM supercomputer, Deep Blue. Kasparov's comments on his wins and losses; Antagonistic perspectives on chess-playing machines; Cultural cogency of the game of chess; Media's unwillingness to attribute superior intelligence or charismatic power to Deep Blue.